Intergenerational Writing Practices in Chinese Fiction for Adolescent Girls. Issue 2 (1st June 2022) - Du, Yan
Abstract: The Anthology of Chinese Fictions on Adolescent Girls' Psychology (2016) is one of the most renowned collections of girls' stories in Chinese children's literature. Authored by Qin Wenjun, Cheng Wei, and Chen Danyan, it is often associated with the rise of shaonǚ xiaoshuo (girls' fiction) in China. In this article, I evaluate the collective writing practices of the women authors mentioned above, focusing, in particular, on how their featured stories address intergenerational dissent and explore models of communication between adolescent girls and women. Highlighting how The Anthology traverses the age divide in a time during which both children's literature and the lives of teenagers underwent significant shifts, I intend to further scholarly understandings of Chinese girls' fiction as a unique literary phenomenon.